Case Report: Preimplantation Genetic Testing and Pregnancy Outcomes in Women With Alport Syndrome - Shi, Wei-Hui; Ye, Mu-Jin; Chen, Song-Chang; Zhang, Jun-Yu; Chen, Yi-Yao; Zhou, Zhi-Yang; Qin, Ning-Xin; Zhou, Xuan-You; Xu, Nai-Xin; Jiang, Zi-Ru; Lin, Jing; Huang, He-Feng; et al. (Frontiers in Genetics, 2021)
Background: Alport syndrome, a monogenic kidney disease, is characterized by progressive hemorrhagic nephritis, sensorineural hearing loss and ocular abnormalities. Mutations in COL4A5 at Xq22 causing X-linked Alport syndrome accounts for 80-85% patients. Three couples were referred to our reproductive genetics clinic for prenatal or preconception counseling. Methods: Prenatal diagnoses were performed by amplifying targeted regions of COL4A5. Targeted next-generation sequencing (NGS)-based haplotype analysis or karyomapping was performed in two patients. Pregnancy outcomes in the three patients were collected and analyzed. Published Alport syndrome cases were searched in Pubmed and Embase. Results: Prenatal diagnoses in two cases showed one fetus harbored the same pathogenic mutation as the proband and the other was healthy. The couple with an affected fetus and the patient with family history of Alport syndrome chose to take preimplantation genetic testing (PGT) procedure. One unaffected embryo was transferred to the uterus and a singleton pregnancy was achieved, respectively. Two patients presented non-nephrotic range proteinuria (< 3g/ 24 h) during pregnancy and the three cases all delivered at full-term. However, published Alport cases with chronic kidney disease or proteinuria during pregnancy were came with a high rate (75%) of adverse maternal and fetal outcomes. Conclusions: The PGT procedure performed in this study was proven to be practicable and might be expanded to be applied in other monogenic diseases. Moderate or severe renal impairments in Alport syndrome were strongly associated with adverse maternal and fetal outcomes and baseline proteinuria was a potential predictor for pregnancy outcomes of Alport syndrome as other kidney diseases.